PENDIDIKAN MULTIKULTURAL DAN GLOBALISASI: UNTUK PROFIT ATAU CULTIVATING HUMANITY? - Baghi, Felix (Jurnal Pendidikan dan Kebudayaan Missio, 2015)
Abstract: Multicultural Education and Globalization: For Profit or Cultivating Humanity? Openness to others is only possible if people learn to look forward, looking at each otherness with the taste of humanity rich in meaning, empathetic. Others in the context of ethical responsibility that asimteris (Levinas), in the light of mutual interpersonal relationships (Paul Ricoeur) and the ability to anticipate the arrival of another absurdity, an anticipation that requires courage to face any situation that could not previously thought (Jacques Derrida), Therefore, adequate education for life in a pluralistic democracy is multicultural education. Multicultural education teaches students to recognize and open to story and narrative of life and culture of other groups, both religious dimension, ethnicity, ekonoms, political and gender. In a global dimension, multicultural education requires interactive contribution of knowledge of history, geography, cultural studies, interdisciplinary, the history of legal and political systems and religious studies.  Keywords: multicultural education, globalization, dialectic pedagogy Abstrak: Pendidikan Multikultural dan Globalisasi: Untuk Profit atau Cultivating Humanity? Keterbukaan terhadap yang lain  hanya mungkin kalau orang saling belajar dengan menatap ke depan, memandang setiap keberlainan dengan cita rasa kemanusiaan yang kaya makna, penuh empati. Yang  Lain dalam konteks tanggung jawab etis yang asimteris (Levinas), dalam terang hubungan interpersonal yang mutual (Paul Ricoeur) dan dalam kesanggupan mengantisipasi kemustahilan kedatangan yang lain, suatu antisipasi yang membutuhkan keberanian untuk menghadapi segala situasi yang tidak dapat diduga sebelumnya (Jacques Derrida). Oleh karena itu, pendidikan yang adekuat untuk hidup dalam suatu iklim demokrasi yang pluralistik  adalah pendidikan yang multikultural. Pendidikan multikutural mengajarkan anak didik untuk mengenal dan terbuka terhadap  kisah dan narasi hidup serta kultur  kelompok yang lain, baik dari dimensi religius, etnis, ekonomis, politis dan gender. Dalam dimensinya yang global, pendidikan multikultural membutuhkan kontribusi interaktif dari pengetahuan sejarah, geografi, studi kebudayaan yang interdisipliner, sejarah hukum dan sistim politik serta studi-studi keagamaan.  Kata kunci: pendidikan multikultural, globalisasi, pedagogi dialektika